Study of the influence of the increased carbon content in electrodes on structure and properties of the welding seam during welding of 110G13 steel - Pashynskyi, Volodymyr; Boyko, Igor (Technology audit and production reserves, 2021)
The object of research is the effect of the carbon-forming component of coated electrodes for welding and surfacing of Gadfield steel (110G13L and analogs) on the structure and properties of the weld. One of the most problematic areas in the welding and surfacing of high-carbon steel is the high irregularity of the rod and coating melting rates. Therefore, the non-melted part of the coating is literally poured into the weld pool, which leads to significant chemical and structural inhomogeneity of the welded metal. The main hypothesis of the study is the assumption that it is possible to increase the homogeneity of the deposited metal by changing the conditions for the transition of carbon from the electrode to the weld pool by using an electrode rod made of carbon steel. In the course of the study, electrode rods with different carbon contents were used. With an increase in the carbon content in the composition of the electrode rod, the fluidity of the drops increased, which contributed to a decrease in the strength of the welding current without harm to the welding and technological characteristics. This allows to reduce the generation of heat in the base metal, that is an effective measure to prevent hot cracks in the weld metal and heat affected zone Studies of the composition of the electrode metal droplets and the weld material showed that with an increase in the carbon content in the electrode rod from 0.08 % to 0.8 %, the carbon content in the droplets increases from 0.3 % to 0.97 %. The carbon content in the weld metal is 1.1 %. The assimilation of manganese by a drop increases with an increasing of coating and the droplet interaction time. A significant increasing in the rate of coating melting was obtained. This is due to the fact that the concomitant decrease in the content of graphite in the coating contributes to a decrease in the refractoriness of the electrode coating. The use of high carbon steels for the manufacturing of electrode rods for welding and surfacing of Gadfield steel improves the properties of the welded metal and sanitary and hygienic parameters.